Step-by-step explanation:
-18.4,-17.3,-1.4,7.8,15.8,16.2
Answer:
1. 15x^7y^2 + 4x^3 => x^3(15x^4y^2 + 4)
2. 15x^7y^2 + 3x => 3x(5x^6y^2 + 1)
3. 15x^7y^2 + 6xy => 3xy(5x^6y + 2)
4. 15x^7 + 10y^2 => 5(3x^7 + 2y^2)
Step-by-step explanation:
To obtain the answer to the question, first let us factorise each expression. This is illustrated below:
1. 15x^7y^2 + 4x^3
Common factor is x^3, therefore the expression is written as:
x^3(15x^4y^2 + 4)
2. 15x^7y^2 + 3x
Common factor is 3x, therefore the expression is written as:
3x(5x^6y^2 + 1)
3. 15x^7y^2 + 6xy
Common factor is 3xy, therefore the expression is written as:
3xy(5x^6y + 2)
4. 15x^7 + 10y^2
Common factor is 5, therefore the expression can be written as:
5(3x^7 + 2y^2)
(D) 33 feet
<u>Explanation:</u>
Given:
Height of the tree, h = 22 feet
angle, θ = 42°
Length of the ladder, l = ?
We know:
sin θ = Perpendicular / hypotenuse
So,
Sin θ = height of the tree / length of the ladder
l = 32.84 feet ≈ 33 feet
Therefore, the length of the ladder be to reach the top of the apple tree is 33 feet.
Answer:
y=2/3x
Step-by-step explanation:
2/3 is greater than 1/2. It doesn't matter if one of the slopes are negative.
Answer:
-8.
Step-by-step explanation:
There’s a minus near the 8, we change it to -8.
y=-8. Hope this helps.